2017
DOI: 10.1136/archdischild-2016-311198
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of chronic fatigue syndrome/myalgic encephalomyelitis in adolescents

Abstract: ObjectiveLittle is known about persistence of or recovery from chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) in adolescents. Previous studies have small sample sizes, short follow-up or have focused on fatigue rather than CFS/ME or, equivalently, chronic fatigue, which is disabling. This work aimed to describe the epidemiology and natural course of CFS/ME in adolescents aged 13–18 years.DesignLongitudinal follow-up of adolescents enrolled in the Avon Longitudinal Study of Parents and Children.Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…As can be seen in Table 2, at T1, participants reported mean scores on the social adjustment scale which surpassed the clinical cut-off threshold of 20 and indicated a moderately severe or worse level of psychopathology (Mundt et al, 2002). They also reported a mean fatigue score which surpassed the cut-off score of 19 out of 33 reported by Norris et al (2017) for chronic disabling fatigue (a proxy for clinician-diagnosed chronic fatigue syndrome). Similarly, participants also reported high levels of fatigue on the fatigue visual analogue scale.…”
Section: Baseline Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…As can be seen in Table 2, at T1, participants reported mean scores on the social adjustment scale which surpassed the clinical cut-off threshold of 20 and indicated a moderately severe or worse level of psychopathology (Mundt et al, 2002). They also reported a mean fatigue score which surpassed the cut-off score of 19 out of 33 reported by Norris et al (2017) for chronic disabling fatigue (a proxy for clinician-diagnosed chronic fatigue syndrome). Similarly, participants also reported high levels of fatigue on the fatigue visual analogue scale.…”
Section: Baseline Characteristicsmentioning
confidence: 96%
“…Research evidence on the trajectory and prognosis of CFS/ME in young people is inconclusive (Gill et al, 2004;Norris et al, 2017;Rangel et al, 2000;Rimes et al, 2007;Sankey et al, 2006). However it has been suggested that CFS/ME should be treated early in order for patients to receive the best outcome (Burgess & Chalder, 2011;Sankey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of fatigue appears to increase as adolescents age. The Avon Longitudinal Study of over 4000 adolescents found that disabling fatigue of greater than six months duration increased from 1.47% to 2.99% between the age of 13 to 18 years [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Crossing over from internet-based CBT to usual care or vice versa, did not influence recovery rates. The trial did not take into account the widely reported spontaneous recovery in adolescents with CFS ( Table 1 ) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], which is similar to or better than the reported recovery rates in this trial. That is without taking into account the problems with the post hoc definition of recovery used by the FITNET trial which was tailor-made to fit the results yet was so wide that it included the severely fatigued/ill.…”
Section: Discussionmentioning
confidence: 64%
“…This is similar to the findings by Rangel et al who found that at a mean follow-up of 38 months, 67% of severely affected patients had recovered [ 40 ] as can be seen in Table 1 . And finally, a recent study by Norris et al (co-authored by the principle investigator of the NHS FITNET trial) entitled “Natural course of chronic fatigue syndrome/myalgic encephalomyelitis in adolescents”, concluded that approximately 75% of adolescents who do not receive treatment will recover after 2–3 years [ 41 ].…”
Section: Issues With the Definition Of Recoverymentioning
confidence: 99%